Large round bale hay wastage by various feeding methods - R.K. Taylor; G.W. Warmann; B.M. Plaschka; Dale A. Blasi; Glenn E. Newdigger Jr. (Kansas Agricultural Experiment Station Research Reports, 1993)
The amounts of wheat or hybrid sudan hay wasted with three large round bale feeding methods were evaluated at two ranch locations. The feeding methods were: 1) bale processor (Hay Forage Industries BP 25®) used to shred forage into bunks; 2) the same processor used to shred forage onto the ground; and 3) unrolling large round bales on the ground. Estimated forage wastages or refusals from unrolling, shredding onto ground, and shredding into bunks were 23, 13, and 8% with wheat hay and 22, 16, and 11% with sudan hay, respectively. These results demonstrate the potential for substantial savings of forage. Shredding or tub-grinding large round bales and feeding in bunks appears to have economic potential when hay prices are high and when herd size is large.
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Feeding management; Feed wastage; Large round bales